2019
DOI: 10.3847/1538-4357/ab26b5
|View full text |Cite
|
Sign up to set email alerts
|

The Cold and Dusty Circumstellar Matter around Fast-expanding Type Ia Supernovae

Abstract: Type Ia supernovae (SNe Ia) play key roles in revealing the accelerating expansion of the universe, but our knowledge about their progenitors is still very limited. Here we report the discovery of a rigid dichotomy in circumstellar (CS) environments around two subclasses of type Ia supernovae (SNe Ia) as defined by their distinct photospheric velocities. For the SNe Ia with high photospheric velocities (HV), we found a significant excess flux in blue light during 60-100 days past maximum, while this phenomenon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 109 publications
7
42
0
Order By: Relevance
“…This is also consistent with the systematically observed blueshifted outflows in the Na I line (Sternberg et al 2011;Maguire et al 2013) in many SNe Ia. In contrast, SNe Ia that do not display HV features and possible evidence of CSM may have double-degenerate progenitor systems (Li et al 2011;González Hernández et al 2012;Schaefer & Pagnotta 2012;Olling et al 2015;Wang et al 2019).…”
Section: Possible Differences Between Sn Ia Populationssupporting
confidence: 86%
See 2 more Smart Citations
“…This is also consistent with the systematically observed blueshifted outflows in the Na I line (Sternberg et al 2011;Maguire et al 2013) in many SNe Ia. In contrast, SNe Ia that do not display HV features and possible evidence of CSM may have double-degenerate progenitor systems (Li et al 2011;González Hernández et al 2012;Schaefer & Pagnotta 2012;Olling et al 2015;Wang et al 2019).…”
Section: Possible Differences Between Sn Ia Populationssupporting
confidence: 86%
“…Wang et al (2013) found that SNe Ia with high Si II velocity (HV SNe Ia) tend to explode at distances closer to the centre of the host galaxies than normal-velocity (NV) SNe Ia and are more likely to be associated with younger stellar environments and metal-rich progenitors. Furthermore, Wang et al (2019) found that HV SNe Ia display a significant excess of blue flux 60-100 days past peak brightness compared to SNe with normal photospheric velocities. This excess may be attributed to light echoes by dust in the CSM.…”
Section: Possible Differences Between Sn Ia Populationsmentioning
confidence: 96%
See 1 more Smart Citation
“…The fractional depth of spectral features in SNe Ia with a larger overall flux levels should be smaller. Wang et al (2019) has suggested that a B-band offset in HV SNe at phases >+40 days could be due to a light echo from circumstellar dust. A light echo could dilute the specral features.…”
Section: Hubble Residuals and Absorption Strengthmentioning
confidence: 99%
“…Further evidence of the presence of a significant amount CSM around SNe Ia came from spectroscopic observations of the narrow Na I D lines. Some SNe Ia show blueshifted and time evolving narrow Na I D absorption lines (Patat et al 2007;Blondin et al 2009;Simon et al 2009;Sternberg et al 2011;Maguire et al 2013;Wang et al 2019). In particular, Wang et al (2009) divided the spectroscopic normal SNe Ia into two groups, the normal-velocity and high-velocity ones with Si II λ6355 velocity lower or higher than 11,800 km/s respectively.…”
Section: Introductionmentioning
confidence: 99%